Pengaruh Model Pembelajaran Student Team Achievement Division (STAD) terhadap Hasil Belajar Siswa pada Mata Pelajaran PPKn Kelas V SDN Semanan 13 Petang - Pratiwi, Dewi Isnania; Hasan, Najib; Sa’odah, Sa’odah (TSAQOFAH, 2023)
This study aims to determine whether there are differences in students' Civics learning outcomes between students who use the Student Team Achievement Division (STAD) learning model and students who use conventional learning methods. This study used the Quasi Experiment research method with the Nonequivalent Control Group Design research design. The population subjects in this study were all fifth grade students at SDN Semanan 13 Petang, totaling 60 students, by taking a sample of two classes of 60 students, namely the VA class which consisted of 29 students as the experimental class and the VB class. consisting of 31 students as the control class. The data collection technique used a multiple choice test with 25 valid and reliable questions. To test the pretest hypothesis in this study using the t-test, the t-test results obtained tcount 1.192 and ttable = 2.0021, meaning that there is no significant effect between the average pretest value of the control class and the experimental class. Whereas for testing the posttest hypothesis from the t-test results obtained tcount = 7.316 and ttable = 2.0021, it can be interpreted that there is a significant influence between the average posttest value of the control class and the experimental class. This can be interpreted that the learning outcomes of students who use the Student Team Achievement Division learning model are higher than those who use conventional learning methods.